Ischemic preconditioning: A practical tool for enhancing exercise performance - Billaut, F.; Mota, G. R. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
This article contains an induction of an adaptive physiological cascade, techniques of ischemic preconditioning, the potential mechanisms and effects of human performance and an outlook to future directions.